2020
DOI: 10.1111/bju.15152
|View full text |Cite
|
Sign up to set email alerts
|

Solitary rib lesions showing prostate‐specific membrane antigen (PSMA) uptake in pre‐treatment staging 68Ga‐PSMA‐11 positron emission tomography scans for men with prostate cancer: benign or malignant?

Abstract: Objectives To determine the proportion of solitary rib lesions on pre‐treatment 68Gallium‐labelled prostate‐specific membrane antigen (PSMA)/computed tomography (CT) scans in men with prostate cancer that are malignant and examine any predictive factors. Patients and methods This retrospective single tertiary referral institution cohort study of men reviewed the results of 68Ga‐PSMA‐11 positron emission tomography (PET)/CT scans performed for primary staging prior to treatment of prostate cancer from July 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Conversely, shoulder girdle and sternal lesions were mostly malignant with 6 PCa metastases out of 7 lesions (85.7%). This is in agreement with the retrospective study by Chen et al 29 where the authors found that 98.4% of the solitary costal bone uptake at PSMA PET/CT during initial staging were benign, as confirmed by PSA negativation after radical prostatectomy. These patterns are consistent with the natural history of PCa.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, shoulder girdle and sternal lesions were mostly malignant with 6 PCa metastases out of 7 lesions (85.7%). This is in agreement with the retrospective study by Chen et al 29 where the authors found that 98.4% of the solitary costal bone uptake at PSMA PET/CT during initial staging were benign, as confirmed by PSA negativation after radical prostatectomy. These patterns are consistent with the natural history of PCa.…”
Section: Discussionsupporting
confidence: 92%
“…In our initial experience, we considered these uptakes as nonspecific, however there was no significant change in size and SUVlmax at follow-up. There is little literature that mentions the nature of these solitary uptake in ribs, however we identified that most of them are of benign origin; taking into account the low uptake of the radiopharmaceutical, the correlation with any signs of trauma and PSA levels [25].…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 patients had corresponding CT findings. Chen et al have reported that 98.4% of the solitary [ 68 Ga] PSMA-11-avid rib foci were benign (19). In a recent retrospective study, the rate of non-specific bone lesions (NSBLs) among PC patients in [ 18 F]PSMA-1007 PET/CT was analyzed (20).…”
Section: Discussionmentioning
confidence: 99%